EFFECT OF DIFFERENT STOCKING DENSITIES ON THE GROWTH AND SURVIVAL OF WHITE LEGGED SHRIMP WITH RED STRAIN TILAPIA UNDER POLYCULTURE SYSTEM - MULE AKASH BABURAO; S. ATHITHAN (The Bioscan, 2020)
The present study was conducted to assess the growth performance of pacific white shrimp (P. vannamei) with red strain tilapia under different stocking densities in indoor rearing. The red strain tilapia fingerlings were acclimatized to live in seawater salinity (35 ppt) by the 40th day of rearing. This experiment was conducted in indoor cement tanks (1.5 × 1.5 × 0.8 m) to observe growth performance of pacific white shrimp with red strain tilapia comprising six treatments and one control) with duplicates. This experiment was conducted for 60 days duration. The mean weight gain of Penaeus vannamei post larvae and red strain tilapia fingerlings reared in seawater showed highly significant positive correlation (p < 0.001) with days of rearing. Two way ANOVA of the data collected clearly affirmed that between different stocking densities and mean body weight gains of Penaeus vannamei and red strain tilapia fingerlings under seawater with days of rearing had significant difference. From this study, among the different stocking densities used for red strain tilapia fingerlings with Penaeus vannamei under polyculture indoor rearing, stocking density of 60 red strain tilapia/m2 exhibited higher growth.